Desire and development - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
This paper explores the impact of gender differences in the desire for sex and the distribution of power in the household on the onset of the demographic transition and the take-off to growth. Depending on the price and efficacy of modern contraceptives, the gender wage gap, and female bargaining power, the economy assumes one of two possible equilibria. At the traditional equilibrium, contraceptives are not used, fertility is high and education and growth are low. At the modern equilibrium, contraceptives are used, fertility is low and further declining with increasing income, and education and growth are high. The theory motivates a "wanted fertility reversal": At the traditional equilibrium, men prefer more children than women whereas at the modern equilibrium, men prefer fewer children than women. Female empowerment nudges households to provide more education for their children and leads to an earlier uptake of modern contraceptives and an earlier onset of the demographic transition and the take-off to modern growth.
Keywords: O40; I25; J10; N30; 330; fertility; sex; contraceptive use; education; economic development